Raw resources of Polygonium minus Huds. in its two populations in Almaty region (Experimental biology, 2015)
The authors point out the location of the natural populations of Polygonum minus, give the results of the study of plant communities in these populations geobotanically, floristic aspects and results of the determination of commodity stocks Polygonum minus in this article.
Keywords: family Polygonaceae Juss; Polygonum minus Huds; medicinal plant; plant association; raw material stocks